Hepatitis E in southern Vietnam: Seroepidemiology in humans and molecular epidemiology in pigs. (9th June 2017) - Berto, A.; Pham, H. A.; Thao, T. T. N.; Vy, N. H. T.; Caddy, S. L.; Hiraide, R.; Tue, N. T.; Goodfellow, I.; Carrique‐Mas, J. J.; Thwaites, G. E.; Baker, S.; Boni, M. F.; et al.
Summary: Viral pathogens account for a significant proportion of the burden of emerging infectious diseases in humans. The Wellcome Trust‐Vietnamese Initiative on Zoonotic Infections (WT‐VIZIONS) is aiming to understand the circulation of viral zoonotic pathogens in animals that pose a potential risk to human health. Evidence suggests that human exposure and infections with hepatitis E virus (HEV) genotypes (GT) 3 and 4 results from zoonotic transmission. Hypothesising that HEV GT3 and GT4 are circulating in the Vietnamese pig population and can be transmitted to humans, we aimed to estimate the seroprevalence of HEV exposure in a population of farmers and the general population. We additionally performed sequence analysis of HEV in pig populations in the same region to address knowledge gaps regarding HEV circulation and to evaluate if pigs were a potential source of HEV exposure. We found a high prevalence of HEV GT3 viral RNA in pigs (19.1% in faecal samples and 8.2% in rectal swabs) and a high HEV seroprevalence in pig farmers (16.0%) and a hospital‐attending population (31.7%) in southern Vietnam. The hospital population was recruited as a general‐population proxy even though this particular population subgroup may introduce bias. The detection of HEV RNA in pigs indicates that HEV may be a zoonotic disease risk in this location, although a larger sample size is required to infer an association between HEV positivity in pigs and seroprevalence in humans.